Understanding the Role of Artificial Intelligent Tools- ChatGPT in Promoting the Learning of English as Foreign Language Case Study of First Year English Students at Mohamed CherifMessaadia University Souk-Ahras - ZEGHADNIA Djamal (My University, 2024)
Abstract This study looks over the current trend in the field of English as a Foreign Language (EFL) which is the use of artificial intelligent technologies- ChatGPT by OpenAI in the learning context. Most notably, the research explores the implications and usefulness of employing such new language model to promote students’ language learning and matery. By integrating surveys, interviews, and number-driven analysis of learning achievements within the mixed-methods framework, this study intended to shed light on the role of using AI-driven platforms by first year English students. Specifically, the focus on engagement, performance improvement, and student attitude towards ChatGPT can help form a comprehensive impression of the advantages and drawbacks of incorporating artificial intelligence into language learning environments. --------------------- الملخص ‫يصف‬‫هذا‬ ‫البحث‬ ‫تطور‬ ‫تعلم‬ ‫اللغة‬ ‫اإلنجليزية‬ ‫كلغة‬ ‫أجنبية‬ ‫‘‬ ‫‪EFL‬‬‫’‬‫من‬ ‫خالل‬ ‫دمج‬ ‫أدوات‬ ‫الذكاء‬ ‫االصطناعي‬ ‫‪.‬‬‫وعلى‬ ‫وجه‬ ‫الخصوص‪،‬‬‫تدرس‬ ‫تأثير‬ ‫وفعالية‬ ‫‘‬ ‫‪ChatGPT‬‬‫’‬‫كنموذج‬ ‫تكنولوجي‬ ‫متطور‬ ‫طورته‬ ‫'‬‫‘‬ ‫‪OpenAI‬‬‫‪،‬‬‫على‬ ‫مستوى‬ ‫اكتساب‬ ‫ال‬ ‫لغة‬ ‫لدى‬‫طالب‬ ‫السنة‬ ‫األولى‬ ‫انجليزية‬ ‫‪.‬‬ ‫استخدمنا‬‫منه‬ ‫ً‬ ‫ج‬‫ا‬‫مختل‬ ‫ً‬ ‫ط‬‫ا‬‫يشمل‬ ‫االستبيانات‬ ‫والمقابالت‬ ‫والتحليل‬ ‫الكمي‬ ‫و‬ ‫النوعي‬‫لن‬ ‫تائج‬ ‫التعلم‬‫‪.‬‬‫يهدف‬ ‫هذا‬ ‫العمل‬ ‫البحثي‬ ‫إلى‬ ‫توضيح‬ ‫تعقيدات‬ ‫اللغة‬ ‫عند‬ ‫استخدام‬ ‫المنصات‬ ‫القائمة‬ ‫على‬ ‫الذكاء‬ ‫االصطنا‬ ‫عي‬ ‫مثل‬‫‘‬‫‪ChatGPT‬‬‫’‬‫في‬ ‫تدريس‬ ‫اللغة‬ ‫اإلنجليزية‬ ‫كلغة‬ ‫أجنبية‬ ‫‪.‬‬‫سمحت‬ ‫دراسة‬ ‫عوامل‬ ‫مثل‬ ‫الدافع‬ ‫وتحسين‬ ‫المهار‬ ‫ات‬‫اللغو‬ ‫ية‬ ‫وتصورات‬‫الطالب‬ ‫لهذا‬ ‫البحث‬ ‫بالمساهمة‬ ‫في‬ ‫فهم‬ ‫أعمق‬ ‫للفوائد‬ ‫والتحديات‬ ‫المحتملة‬ ‫المرتبطة‬ ‫بدمج‬ ‫الذ‬ ‫كاء‬‫اال‬ ‫صطناعي‬‫في‬ ‫سياقات‬‫تعلم‬ ‫اللغة‬ ‫‪. --------------------- ‬‬Résumé Cette recherche décrit l’évolution del’apprentissage de l’anglais langue étrangère (ALE) à travers l’intégration des outils de l’intelligenceartificielle. Elle étudienotammentl'impact et l'efficacité de ChatGPT en tantquemodèletechnologique de pointe développé par OpenAI, au niveau de l'acquisition de la langue par les étudiants de première année langue anglaise. Nous avonsutiliséuneapproche à méthodesmixtescomprenant des questionnaires, des entretiens, uneanalyse quantitative et qualitative des résultatsd'apprentissage. derecherche vise à clarifier les subtilités de la langue lors Cetravail de l'utilisation de plateformesbaséessurl'IAcommeChatGPTdansl'enseignement de l’anglais langue étrangère. L’étude desfacteurstelsque la motivation, l’amélioration des compétenceslinguistiques et les perceptions des étudiantssurl’emploi de ChatGPT, a permis à travers cetterecherche de contribuer à unecompréhension plus approfondie des avantages et des défispotentielsassociés à l’intégration de l’IAdans les contextesd’apprentissage des langues.